Disease severity and associated family impact in childhood atopic dermatitis. Issue 5 (1st May 2003) - Balkrishnan, R; Housman, T S; Carroll, C; Feldman, S R; Fleischer, A B
Abstract : Aim: To examine the association between childhood atopic dermatitis (AD) severity and family impact at baseline and after an intervention by a physician specialist, using validated measures of both severity and family impact. Methods: Cross sectional self administered survey of parent–caregivers of 49 randomly selected children with AD; 35 parents were available for follow up. Family impact was measured using a modified AD Family Impact Scale completed by the parent–caregiver. The child's disease severity was measured using both the investigator's assessment via the Eczema Area and Severity Index (EASI) and the caregiver's assessment via the recently validated Self Assessment Eczema Area and Severity Index (SA-EASI). Results: The parent–caregiver's assessment of severity of the child was the most significant correlate of the family impact of the child's AD (p = 0.65 at baseline and p = 0.38 at follow up). In multivariate regression models, the parent–caregiver's estimate of severity remained the single strongest predictor of family impact before and after receipt of dermatologist care, as well as the difference in impact between pre and post-dermatologist care. Conclusions: There is evidence to support the ability of parent–caregivers of children with AD to accurately determine severity of their child's AD; perceived severity is the driver of the family impact of this condition. Treatment of a child by a physician specialist is associated with reductions in both perceived severity, as well as family impact of this condition.